Hypercoagulability sState in celiac disease and hepatitis C association - Aldea, Cornel; Sur, Daniel; Silaghi, Ciprian (International journal of celiac disease, 2018)
A concerning pathological and serological aspect that is found in both HCV and celiac disease is the hypercoagulability state which can lead to various complications.
Keywords: jaterní cirhóza; nedostatek vitaminu K; Vitamin K Deficiency; hepatitida C; Liver Cirrhosis; Hepatitis C; Humans; trombofilie; Thrombophilia; lidé; Celiac Disease; celiakie